ANALISIS KESULITAN BELAJAR MAHARAH KALĀM SISWA KELAS VIII DI SMP TAHFIDZ PLUS KHOIRU UMMAH SEPANJANG SIDOARJO - Fauzi, Rif El; Ammar, Farikh Marzuki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors that contribute to learning difficulties in speaking skills (maharah kalām) among eighth-grade students at SMP Tahfidz Plus Khoiru Ummah Sepanjang Sidoarjo. A descriptive qualitative approach was employed, using interviews and observations as data collection techniques. The findings reveal that both internal and external factors influence students’ challenges in speaking Arabic. Internal factors include limited active vocabulary, difficulty in understanding Arabic grammar structures (nahwu and sharaf), feelings of shyness and low self-confidence, as well as uneven learning motivation. External factors consist of the use of conventional teaching methods, limited time allocated for speaking practice, and an underdeveloped Arabic-speaking environment (bi’ah lughawiyah). To address these issues, this study recommends increasing the frequency and quality of speaking practice, establishing a supportive language environment, and adopting more varied and communicative teaching methods. These findings are expected to serve as a foundation for developing more effective teaching strategies to enhance students' Arabic speaking skills